SISTEM INFORMASI AKUNTANSI DISTRO REBORN VINTAGE APPAREL - Stefanus Tegar Kurniawan (Universitas Tulungagung, 2022)
ABSTRACT This study aims to find out how the application of Accounting Information Systems in the fashion industry is more directed at the distribution sector. The method of data analysis in this study used a descriptive method so that in collecting data the author carried out an observation method, which then the results will be described in accordance with what is when collecting data. The results of this study prove that an Accounting Information System must exist in every field or sector of the company, not least in the textile industry sector which is more directed to the distribution sector. However, there are still many actors in the fashion industry who have not implemented the Accounting Information System properly and correctly. Therefore, we will review a little and describe it according to the data and observations we made in the field, so that the paper we provide can be a source of information and evaluation material for the sector we are discussing. ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana penerapan Sistem Informasi Akuntansi dalam bidang industry fashion yang lebih menjurus pada sector Distro. Metode analisis data dalam penelitian ini menggunakan metode deskriptif sehingga dalam mengumpulkan data penulis melakukan metode observasi yang selanjutnya hasilnya akan dijabarkan sesuai dengan apa adanya saat pengumpulan data. Hasil penelitian ini membuktikan bahwa Sistem Informasi Akuntansi harus ada di setiap bidang atau sektor perusahaan, tak terkecuali dalam Bidang industry fashion yang lebih menjurus pada sector Distro. Namun bagi para pelaku dalam bidang industry tekstil masih banyak yang belum menerapkan Sistem Informasi Akuntansi dengan baik dan benar. Maka dari itu kami akan mengulas sedikit dan menjabarkan sesuai dengan data dan observasi yang kami lakukan di lapangan, agar boleh makalah yang kami sediakan ini bisa menjadi sumber informasi dan bahan evaluasi bagi sektor yang kami bahas.